Codes de conduite et systèmes d’alerte éthique : La RSE au sein des chaînes globales de valeur - Corinne Vercher; Florence Palpacuer; Sandra Charreire Petit (Revue de la Régulation)
This article investigates the nature and influence of Corporate Social Responsibility (CSR) within the context of Global Value Chains (GVCs). CSR is approached on the basis of a comparison between two distinct managerial tools – whistleblowing and codes of conduct – adopted by corporations in order to enhance ethical practices at opposite ends of GVCs, either in financial reporting to shareholders (whistleblowing), or in suppliers’labor practices (codes of conduct). Despite highly specific contexts and modes of operation, we observe that these CSR tools share three common characteristics on which we assess their effectiveness on the basis of criteria drawn from an institutional view of CSR.